SMART LIBRARY SYSTEM – INNOVATION IN LIBRARIES WITH A SMART BOOK PRINTER. - Davlatova Nurjahon (TADQIQOTLAR, 2026)
Abstract: This article explores the "Smart Library System" project, which aims to address issues in the automation and standardization of library services. The project centers around an innovative "smart book printer" that allows users to print electronic books in a physical format. The main goal is to encourage the younger generation to read more and familiarize themselves with new technologies. This article discusses the technological features, practical benefits, and social significance of the "Smart Library System" project.